Estimation of the Lithuanian Population Structure by Ethnolinguistic Groups - Jakaitienė, Audronė; Kučinskas, Vaidutis (Lithuanian Journal of Statistics, 2013)
The studies about the homogeneity of the Lithuanian population according to ethnolinguistic groups were carried out in various areas – psychological, anthropological, genetic, etc. From diverse research results, we know that the ethnic Lithuanian population is not homogeneous. For the analysis of the Lithuanian population according to ethnolinguistic groups, one should first know the population structure according to the mentioned groups so that a two-stage stratified random sample could be drawn. As to author’s knowledge, there are no publications about the structure of the Lithuanian population by ethnolinguistic groups. Statistics Lithuania does not produce such information. In the paper, the expert estimation of the Lithuanian population structure by ethnolinguistic groups is provided, based on annual population figures at the beginning of the year (2001–2013) from Statistics Lithuania. According to final 2001 and preliminary 2011 population census data, it was calculated that the ethnic Lithuanian population consists of 24.5 per cent of žemaičiai and 75.5 per cent of aukštaičiai. The latter is rather the estimation of the Lithuanian population structure living in the ethnolinguistic areas than the structure of the Lithuanian population by ethnolinguistic groups. Therefore, the results obtained should be used as an approximate estimate of the Lithuanian population structure by ethnolinguistic groups in empirical studies.